RELENDO CHANDLER, WILLIAMSON E NORTH PARA ENTENDER O PROCESSO DE FORMAÇÃO DAS ESTRADAS DE FERRO NO BRASIL - Staduto, Jefferson Andronio Ramundo; Rocha Jr, Weimar Freire da; Freitas, Clailton Ataídes de (Análise Econômica, 2009)
This paper examines the process of creation of the great and "modern" Brazilian railway companies in the century XIX, highlighting specially, São Paulo railway companies that appeared harnessed to the coffee economy. This exam is accomplished to the mode of some of the theorical approaches of the Chandler, Williamson, North and others.